METHODOLOGICAL FUNDAMENTALS OF THE PROJECT "METHODICAL SUPPORT FOR THE PROFESSIONAL DEVELOPMENT OF A BACHELOR OF PEDAGOGICAL EDUCATION" - Lyudmila M. Kalninsh (Высшее образование в России, 2016)
The materials of the article present the methodological fundamentals of the project "Methodical support for the professional development of a bachelor of pedagogical education". The authors outlines the essence of the system of methodological support of a Bachelor of education in his (her) independent professional activity. This new form of teacher skills training uses Internet community and Internet resources and provides a continuing self-regulated process of professional development.